(untitled) (The Journal of Plant Protection Sciences, 2022)
Cowpea (Vigna sinensis) has been considered as an important legume fodder and green manure crop during pre-kharif and kharif season. It has been considered even better in performance than maize. In some parts of India it is also used as green vegetable and pulse. The crop is known to suffer from a variety of diseases. Among those root rot and collar rot are important and R. solani has been an important factor behind these two main diseases. A field trial was conducted during pre-kharif season of 2011 to control root and collar rot of cowpea caused by Rhizoctonia solani with two organic formulations of Trichoderma harzianum along with other treatment combinations. It was observed that seed priming with mycelia preparation of the antagonist Trichoderma harzianum at 4g/kg of seed and organic formulation of the antagonist in vermicompost along with 20% neem cake (w/w) gave best disease control along with yield of cowpeas over leaf mold +20% neem cake formulation of the antagonist, talc base formulation and seed treatment with carbendazim at 2g/kg of seed. Seed priming with mycelial mat of the antagonist improved seed germination vigour of the cowpea plants, basal girth, number of branches & pod number, pod vigour of the bio primed seeds over other treatment combinations. Soil application of Trichoderma in vermicompost +20% neem cakes gave better disease control over the others.